Making sense of financial vulnerability: Between sensitivity, resilience, and exposure - Valentin Voith; Sandra Mauser (Oesterreichische Nationalbank (OeNB), 2024)
Economic uncertainty has increased globally in the previous years, affecting households and individuals in their financial lives. Policymaking bodies are confronted with the task to stem the loss of prosperity and providing help to financially vulnerable people. Empirical research uses various approaches to conceptualize financial vulnerability, whereby the respective assumptions yield important implications for derived policy measures. In this paper, a theoretical framework will be elaborated such that existing research can be interpreted and made comparable on common grounds. We understand financial vulnerability, which we define as the likelihood to fall into financial hardship, as a three-dimensional model, namely a function of (1) sensitivity, i.e., objective factors outside the immediate sphere of influence, (2) resilience, i.e., subjective capacities to cope with and to adapt to financial shocks, and (3) exposure, i.e., the probability to encounter a financial shock. With this conceptualization financial vulnerability due to structural societal inequalities can be distinguished from financial vulnerability due to unsound financial decision-making and, therefore, offers a clearer understanding of which policy measures are needed to support people in their financial lives. In this context, special emphasis is placed on the potential role of financial education. An empirical analysis using the Austrian dataset of the OECD/INFE Adult Financial Literacy Survey 2019 is included to demonstrate the applicability of our theoretical framework.
Keywords: D14; I32; G53; 330; financial vulnerability; financial resilience; financial shocks; financial hardship; financial literacy